13C‐Labeled Diethyl Ketoglutarate Derivatives as Hyperpolarized Probes of 2‐Ketoglutarate Dehydrogenase Activity. Issue 4 (11th August 2021) - Singh, Jaspal; Suh, Eul Hyun; Sharma, Gaurav; Chen, Jun; Hackett, Edward P.; Wen, Xiaodong; Sherry, A. Dean; Khemtong, Chalermchai; Malloy, Craig R.; Park, Jae Mo; Kovacs, Zoltan
Abstract: The TCA cycle is a central metabolic pathway for energy production and biosynthesis. A major control point of metabolic flux through the cycle is the decarboxylation of 2‐ketoglutarate by the TCA cycle enzyme 2‐ketoglutarate dehydrogenase (2‐KGDH). In this project, we developed 13 C labeled 2‐ketoglutarate derivatives to monitor 2‐KGDH activity in vivo. 13 C NMR analysis of liver extracts revealed that uniformly 13 C labeled 2‐ketogutarate, in its cell permeable ester form, was rapidly taken up and hydrolyzed in liver and underwent extensive metabolism to produce labeled glutamate, succinate, lactate and other metabolites. Diethyl [1, 2‐ 13 C2 ]‐2‐ketoglutarate was successfully polarized by dynamic nuclear polarization and within seconds after injection into rats, the probe produced hyperpolarized [ 13 C]bicarbonate in the liver reflecting flux through the TCA cycle. These experiments demonstrate that this tracer offers the possibility of directly monitoring flux through 2‐KGDH in vivo. Abstract : The 2‐ketoglutarate dehydrogenase catalysed decarboxylation of 2‐ketoglutarate is an important control point of metabolic flux in the TCA cycle. Here, we demonstrate that hyperpolarized diethyl [1, 2‐ 13 C2 ]‐2‐ketoglutarate is rapidly taken up by the liver and hydrolyzed to the free acid, which enters the TCA cycle and undergoes decarboxylation to produce hyperpolarized bicarbonate. These data indicate that this hyperpolarized tracer could be used to monitor flux through 2‐ketoglutarate dehydrogenase in vivo.